How Gaming Applications of CALL influence inputs of English Grammar - Alsuhaymi, Atif Obaid (Journal of Educational and Psychological Sciences, 2020)
The present study aims to research the influences of games through Computer-Assisted Language Learning (CALL) compared to Teacher-Centered Instruction (TCI) on teenagers' achievement in English language education in Saudi Arabia. Two groups of students tested, before and after instruction, so to determine success of the application of pedagogies. The full sample consisted of 22 teenagers, divided randomly, into two equal groups. The first group was the control (TDI) group, which used a school textbook. The second group was the experimental group (CALL), which given a CALL application, based on the game ‘Kahoot.’ Two types of tests were conducted, a pre-test and a post-test, at each of two periods for each group. The pre-test administered before instruction, and the post-test taken after the instructional period. Findings indicate that both groups increased their proficiencies with English object pronouns. However, performance on the post-test by the experimental (CALL) group significantly exceeded that of the control (TCI) group.
Keywords: Computer assisted language Learning (CALL); CALL; Games; English grammar; Teacher-Center Instruction (TCI); TCI